منهج القرآن الكريم في تهذيب شهوة الجنس (قصة يوسف عليه السلام أنموذجا) - Abdul Fatah Abdul Majid Aran
This study tackles one of the most important issues in relation to the morals in Muslim society which is the issue of reforming and purifying the soul and hearts through highlighting the issue of refining and discipline the lust of sex in the Holy Quran context specially in Surat Yusuf in order to keep the Muslim religion and the Muslim life away from any vice. The objective of this study is to present the Quranic verses in Surat Yusuf which includes much moral legislations and presented the right morals original which discipline the lust of sex and follow the right path based on Allah Law such these morals are chastity and restricting the lust in the soul. This study highlights the causes of stimulating the lust and committing the outrageous such as men and women mix in the same place and meeting man and woman lone, seduction and the initiatives of the adultery. As for the problem which this study was carried out. It lies on learning the Qur'anic solutions transmitted in Surat Yusuf to control sexual arousal, refine it, and avoid its negative effects, in light of the spread of sexual stimuli the easy access to it. The inductive and analytical approaches are used in this study via tracing the Quran verses that are related to the subject matter of this study namely, in Surat Yusuf .Then the researcher analysed them depending on the ancient and contemporary books of interpretations as well as the books of education and purification. This study reached the most important results: Armament of the soul with useful science is an important means for advancing the members of society to be elements of building and strength and to leave the sordid and superstitious things, Adherence to the etiquette of the Noble Qur’an and the principles of true Islam which are the most effective medicine and the most beneficial treatment to refine desires and eliminate abnormal sexual orientation, Instilling full faith in the souls, which helps them to stand firm in the face of temptation and when fear of falling into sins, Exercising Yusufic morals to achieve chastity, which is the happiness of all mankind.